Public finance, political manoeuvering, and the role of independent and controlled commissions: contrasting experience of the Finance and Planning Commissions in India - Ahmad, Masroor (2016)
Normative theories of public finance, focusing on equity and efficiency criteria, have not been able to explain fully the variations in shares of different sub-national governments in intergovernmental transfers. This has led to an increase in empirical literature which considers the role of political factors, along with equity and efficiency criteria, in the allocation of central resources to subnational levels. Some of this literature recognises that funds transferred through independent constitutional bodies and other agencies may not be affected by political considerations in the same ways and to the same extent. Consistent with this recognition, this study of the experience of the Finance and Planning Commissions in India examines whether transfers to subnational governments are less prone to political manoeuvering if facilitated through an independent body. The study reveals that transfers through a constitutional body are less prone to political interventions than transfers via a body headed by political executives. The findings of the study have broader policy implications in terms of independent institutional interventions assisting in mitigating political distortions in central transfers. - Reproduced.
Keywords: Finance Commission - India; Public finance - India; Finance Commission; Public finance